Status gizi, asupan zat gizi mikro (kalsium, magnesium) hubungannya dengan sindroma premenstruasi pada remaja putri SMU Sejahtera di Surabaya - Irine Christiany; Mohammad Hakimi; Toto Sudargo (Jurnal Gizi Klinik Indonesia, 2009)
Background : Premenstrual syndrome generally known as the interruption the existing hormonal changing during menstrual cycle that will disturb the emotional and physical comfortable. It works on women during the reproductive age. The syndromes are denoted by the amount of signs and symptoms that occurred during fase luteal at the menstruation cycle. Psycho-emotional problems are more than common premenstrual complaint, although physical anxiety more often occurred during menstruation period. Factors of micronutrient intake (calcium, magnesium) greatly affect mood and behavior during premenstrual syndrome.Objective : The study was to identify relationship between nutritional status, micronutrient intake (calcium, magnesium), and premenstrual syndrome among female adolescence.Method : The study was observational or non-experimental which used cross sectional design. The populations were female adolescence of Sejahtera Senior High School at Surabaya. Samples were taken using total sampling technique because the subject had been determined to those aged 16–18 years. As many as 97 people fulfilled inclusion criteria. Data processing and analysis used univariable, bivariable, and multivariable techniques. Statistical test used logistic regression. Result : The result of the study showed that there was no significant relationship between good nutritional status and occurence of premenstrual syndrome (p = 0.086; OR = 2.278; 95% CI = 0.980-5.295), between calcium intake and premenstrual syndrome (p = 0.032; OR = 2.910; 95% CI = 1.176-7.200), between magnesium intake and premenstrual syndrome (p = 0.012; OR = 3.319; 95% CI = 1.369-8.043). There was significant relationship between calcium and magnesium intake and premenstrual syndrome. Conclusion : The result of multivariable analysis showed that nutritional status, intake of calcium and magnesium had significant relationship with premenstrual syndrome.